Genetic Causal Relationship Between Sex Hormones and Basal Cell Carcinoma: A Two-Sample Mendelian Randomization Study - Luo P; Gao D; Wang C; Guo R; Zhang Q (Dove Medical Press, 2024)
Pan Luo, Dejin Gao, Chenglong Wang, Rui Guo, Qingguo Zhang Department of Auricular Reconstruction, Plastic Surgery Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of ChinaCorrespondence: Qingguo Zhang; Rui Guo, Department of Auricular Reconstruction, Plastic Surgery Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, 33 Badachu Road, Shijingshan District, Beijing, People's Republic of China, Email plastic369@163.com; guorui0114@163.comBackground: The primary aim of this study was to explore whether sex hormones affect the occurrence of basal cell carcinoma (BCC) from a genetic perspective using a two-sample Mendelian randomization (MR) study.Methods: Exposure and outcome data for this MR analysis were derived from previously published GWAS studies. In this study, estradiol, sex hormone-binding globulin (SHBG), bioavailable testosterone, and total testosterone were used as exposures, and BCC was used as the outcome for the two-sample MR analysis. The random effects inverse variance weighted (IVW) model was the primary analytical model, and the simple mode, weighted median, MR-Egger, and weighted mode methods were applied as complementary approaches. Furthermore, the "leave-one-out" sensitivity analysis was performed to assess stability, Cochran's Q test to evaluate heterogeneity, and the MR-Egger intercept test to analyze horizontal multiplicity.Results: The two-sample MR analysis of the sex hormone and BCC showed that estradiol, sex hormone-binding globulin (SHBG), bioavailable testosterone, and total testosterone were not a causal factor in BCC (P> 0.05). The results of the heterogeneity test and horizontal pleiotropic analysis showed that no heterogeneity or horizontal pleiotropic existed in all MR analyses (Cochran's Q-P> 0.05, Egger intercept-P> 0.05).Conclusion: The two-sample MR analysis showed that estrogen and testosterone did not affect the occurrence and development of BCC at the genetic level.Keywords: sex hormone, basal cell carcinoma, Mendelian randomization study, genetics, causal relationship